Exploring Task-Based Language Teaching in EFL Contexts: Instructor Perspectives on Challenges and Effective Strategies for Enhancing Speaking Skills - Wu, Yuanyuan; Noordin, Nooreen; Razali, Abu Bakar (Journal of Qualitative Research in Education, 2026)
This paper discusses how English as a Foreign Language (EFL) instructors perceive the use of Task-Based Language Teaching (TBLT) in facilitating speaking skills in Chinese EFL contexts. The study employs a qualitative descriptive research design because it seeks to explore the perceived barriers and effective teaching methods associated with task-based speaking instruction. Semi-structured interviews were used to collect data by interviewing twelve EFL instructors in universities and language institutions in China, which was complemented by reflective notes. Thematic analysis was employed to analyze the data. The results have shown that instructors are struggling with a number of problems, such as large class sizes, difficulties in assessing speaking achievement, lack of motivation among students, and limited institutional resources. Regardless of these limitations, the instructors mentioned using successful strategies such as task adaptation and scaffolding, flexible grouping techniques, and formative feedback practices to support student participation and communicative engagement. The findings indicate that TBLT has great potential to enhance speaking skills, but its effectiveness is highly reliant on whether the instructors can adapt the principles of tasks to the reality of contexts. The paper highlights the need to synchronize assessment activities with communicative purposes and institutional support of task-based pedagogy. Curriculum designers and policymakers are encouraged to develop flexible assessment systems and professional development programs that focus on enhancing the effective implementation of TBLT in EFL speaking instruction.